Wi-Fi Based Indoor Navigation System For Campus Directions - Magsi, S.A. (Institute of Electrical and Electronics Engineers Inc., 2021)
Car navigation systems have made place everywhere around the globe. Outdoor navigation systems can be widely located in almost every geographical location that has access to the internet. However, indoor navigation system is very important for the pedestrians to find out their ways in complicated indoor areas such as shopping malls, subways, universities, exhibitions, underground areas, and tunnels etc. The recent rapid expansion of Wi-Fi zones and the increase of Wi-Fi equipped smartphones have enabled transformation of this idea to the reality. This work presents university indoor navigation system designed to help students, staff, and visitors to find their desired location. The work shows promising results when using distance measuring algorithm, the Trilateration, and the ITU-R P.1238 model together using the Network Simulator 2 'NS2' for the indoor navigation. Â© 2021 IEEE.